HUBUNGAN ANTARA MINAT MEMBACA DENGAN KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS V SD GUGUS VII MENGWI TAHUN AJARAN 2017/2018 - Dewa Ayu Putri Pratiwi (Universitas Pendidikan Ganesha, 2018)
This research aims to determine the significant relationship between reading interest with the skills of short story writing of 5th grade students of elementary school in Gugus VII Mengwi, academic year 2017/2018. This research was ex pos facto, correlational research. The population of this research was the entire 5th grade elementary students in Gugus VII Mengwi academic year 2017/2018 which amounted to 186 students. Sample determinated using proportional random sampling technique with 5% error rate so that the number of samples obtained from the population was 123 students. Interest reading data was collected by giving a questionnaire to the research sample, while the data of short story writing skill was obtained from the description test. As a prerequisite test was the normality test of data distribution. After the prerequisite test is met, and the normal distributed data statistical analysis used in this research was the product moment correlation analysis technique. Based on data analysis obtained thitung = 0,480, while at 5% significant level with n = 123, then the value obtained ttabel = 0,176. Because thitung>ttabel then the null hypothesis (H0) that states there is no significant relationship between reading interest whit the skills of short story writing of 5th grade students of elementary school in Gugus VII Mengwi academic year 2017/2018 rejected and the alternative hypothesis (Ha) accepted. In conclusion, there was a significant relationship with a weak level relationships and occurred in the form of a positive relationship between reading interest with short story writing skill of 5th grade students of elementary school in Gugus VII Mengwi academic year 2017/2018.